2006
DOI: 10.1089/vim.2006.19.237
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Short Recombinant C4V3 HIV-1 Immunogen That Induces Strong Anti-HIV Responses by Systemic and Mucosal Routes Without the Need of Adjuvants

Abstract: Synthetic peptides have been shown to evoke neutralizing and cytotoxic protective anti-HIV responses in mice and other animal models. Recent data support that C4V3 peptides can induce anti- V3 antibodies that neutralize primary isolates. Critical to the success of peptide-based vaccines is the development of strategies to augment their immunogenicity while reducing their large-scale production costs. Therefore, finding efficient and economical alternatives for the production of epitopic vaccines could have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…5a-c). However, the molecular weight of the immunoreactive protein was higher than expected, as previously noted by Varona-Santos et al (2006). These results suggested that tobacco chloroplasts were capable of expressing the C4V3 and retaining its antigenic determinants.…”
Section: Detection Of the C4v3 Transgene In Tobacco Plantssupporting
confidence: 71%
See 4 more Smart Citations
“…5a-c). However, the molecular weight of the immunoreactive protein was higher than expected, as previously noted by Varona-Santos et al (2006). These results suggested that tobacco chloroplasts were capable of expressing the C4V3 and retaining its antigenic determinants.…”
Section: Detection Of the C4v3 Transgene In Tobacco Plantssupporting
confidence: 71%
“…Previously, we have reported on the production of the C4V3 protein at high levels in recombinant E. coli, demonstrating that despite its low molecular weight, the recombinant C4V3 could induce strong humoral immune responses against HIV-1 sequences when delivered by systemic and mucosal routes, even without the aid of adjuvants (Varona-Santos et al 2006). In this study, we have engineered tobacco plants to produce a plastidexpressed C4V3 protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations